Initiating Hypertension Prevention Based on the Health Belief Model among Coastal Fishing Communities in Pangandaran - Maziyya, Nur; Febrianto, Firman; Sri Wijayanti, Lady Ayu (Farmers: Journal of Community Services, 2025)
Fishermen are a population at high risk for hypertension due to heavy physical activity, high sodium dietary patterns, and limited access to healthcare services. Bojongsalawe is a coastal hamlet located in Parigi, Pangandaran, where the majority of the residents work as fishermen. This community service activity aimed to conduct blood pressure screening and provide health education about hypertension risk of fishermen in Bojongsalawe Hamlet. The methods used included direct blood pressure measurement and health counseling following the screening. A total of 20 fishermen participated in the activity. The screening results showed that one person had hypertension, while the other 19 had normal blood pressure. The participants showed great enthusiasm throughout the activity. The education provided covered understanding of risk factors, signs and symptoms, hypertension complications, and prevention strategies. Subjective evaluation results indicated that this activity was effective in increasing early awareness of hypertension and the importance of early detection among fishermen. Simple screening activities accompanied by health education can serve as promotive and preventive efforts that are beneficial in controlling hypertension in coastal communities, particularly among fishermen.